Perspectives on Engagement With Youth Physical Activity Opportunities in Low-Income, African American, Urban Neighborhoods. Issue 1 (January 2023) - Suminski, Richard R.; Robson, Shannon M.; Kopetsky Fultz, Amanda; Sundermeir, Samantha M.; Jahnke, Sara A.
Purpose: To identify and describe factors related to low-income, African American youth's participation in neighborhood youth physical activity opportunities (YPAO). Approach: Formative research. Setting: Face-to-face focus groups in New Castle County, Delaware. Participants: Fifty-five adults (parents/guardians of youth, YPAO providers, small business representatives) living and/or working in low-income, African American neighborhoods. Method: Nine, 60-90 minute focus groups were conducted from December 2018 through March 2019. Focus group questions were developed a priori and included domains related to neighborhood YPAOs. The domains were awareness of YPAOs, benefits and barriers to providing YPAOs, ways to increase youth participation in YPAOs, and strategies for creating, improving, and sustaining YPAOs. Focus group recordings were transcribed, and thematic analysis was performed to identify themes related to increasing youth participation in YPAOs. Results: Four major themes related to YPAOs emerged: 1) exposure/access, 2) parent buy-in/accountability (e.g., personal values and trust with YPAOs), 3) technology, and 4) increasing a sense of community. Three minor themes included liability, advertising, and schools. Small businesses desired to support YPAOs mainly through non-monetary means, while mutually benefitting from receiving local recognition. Conclusion: Developing strategies to incorporate effective community partnerships, creative program ideas with advertising, and active, multisector involvement including small businesses into practice has the potential to increase engagement of low-income, African American youth in YPAOs.